Supply Chain Management for dummies - Stanton, Daniel (John Wiley & Sons, Inc., 2023)
Supply Chain Management For Dummies gives you the full rundown on what a supply chain is, how it works, how to optimize it, and the best education for a rewarding supply chain career. This new edition is fully updated for changes to the supply chain in a post-Covid world. You'll learn about the latest supply chain technologies, analytics and data-based optimization, and new strategies for delivering on your organization's promises. This approachable resource can take your supply chain management skills to the next level with step-by-step explanations, expert tips, and real-life examples. Gain a foundational knowledge of issues in supply chain management. Learn about today's global supply chains, plus trends like reshoring and near-shoring. Wrap your mind around how an organization's moving parts can be coordinated in today's high-tech world. Discover strategies for dealing with disruptions, focusing on diversity, and increasing resilience This For Dummies guide is great for entry-level supply chain professionals and anyone who needs an update on need-to-know concepts and recent changes in supply chain management.